Using Neuroevolution to Design Neural Networks [special issue] - Castelli, Mauro (2020)
Castelli, M. (Guest ed.), Medvet, E. (Guest ed.), Trujillo, L., & Manzoni, L. (Guest ed.) (2020). Using Neuroevolution to Design Neural Networks. Computational Intelligence And Neuroscience, 2020.